Interpersonal Relationships in Education An Overview of Contemporary Research - Wubbels, Theo.; Brok, Perry den.; Tartwijk, Jan van.; Levy, Jack.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This book brings together recent research on interpersonal relationships in education. Clearly, positive teacher-student relationships strongly contribute to student learning. Problematic relationships on the other hand can be detrimental to student outcomes and development. Productive learning environments are characterized by supportive and warm interactions throughout the class: teacher-student and student-student. Similarly, teacher learning thrives when principals facilitate accommodating and safe school cultures.The contributions to this book are based on presentations at the first International Conference on Interpersonal Relationships in Education: ICIRE 2010 held in Boulder, Colorado, the United States and include among others keynote addresses by Kathryn Wentzel, Walter Doyle and Theo Wubbels. The chapters help explain how constructive learning environment relationships can be developed and sustained. Contributions come from among others educational and social psychology, teacher and school effectiveness research, and communication and language studies, among other fields. They cover relationships of teachers with individual students and among peers, and relationships between teachers and teachers and principals.
Keywords: Education; Education; Education (general).